Mentor teachers’ and student teachers’ experiences on teaching practice: an influx of teachers in training - Zondo, Sindiswa Silindokuhle; Adu, Emmanuel Olusola (Eureka, Social and Humanities (Online), 2024)
This study examined mentor teachers' and student teachers’ experiences in teaching practice and examined how student teachers can be prepared to meet mentor teachers’ expectations. This interpretive qualitative case study purposively sampled three secondary schools, and in each research site, two student teachers and two mentor teachers were sampled respectively. Semi-structured face-to-face interviews and focus group interviews with student teachers and mentor teachers were used as data collection methods. The findings reported that participants perceived teaching practice as an important exercise for student teachers and this is where student teachers receive in-service practical in-house training to apply pedagogical theoretical knowledge into practice. Mentor teachers were not pleased by the unprofessional behavior, demonstrated by student teachers, and thus perceived teaching practice value as depreciating. The large number of student teachers, placed in the schools, was overwhelming and mentors felt overcrowded. The findings revealed that mentor teachers felt insufficient as they did not understand their role as mentor teachers. The mentor teachers perceived modules, offered in universities, as rigid and outdated, thus suggested the introduction of coding and robotics subjects in their module packing. Inversely, student teachers were reported discouraged and unhappy as mentor teachers perceived them as a relief, and learner indiscipline emerged as a problem for all student teachers. Quality of learners was a concern for student teachers and remarkably, daunted/killed their love and passion for the teaching profession. The study recommends a relationship between teachers' training institutions, schools, and the Department of Basic Education and workshops for mentor teachers.